2014
DOI: 10.1007/s11947-014-1422-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Stability of Edible Lycopene-Containing Micro- and Nanocapsules Produced Through Electrospraying and Spray Drying

Abstract: In this work, lycopene was encapsulated through electrospraying and spray drying (using a microporous membrane cap) within different edible biopolymeric matrices. Specifically, dextran, a whey protein concentrate (WPC) and chitosan were used as matrix materials. As a strategy to incorporate the hydrophobic bioactive within the hydrophilic matrices, emulsion electropraying and spray drying from emulsion were carried out. Moreover and, for comparison purposes, coaxial electrospraying was also performed. The elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 24 publications
5
63
1
Order By: Relevance
“…Lycopene is a naturally occurring red carotenoid pigment present in tomatoes, watermelon, pink grapefruit, pink guava and papaya (Sinha & Dua, ) with health benefits associated with lower risk of some degenerative diseases that may play a specific role in preventing prostate cancer and cardiovascular disease (Costa‐Rodrigues et al ., ). Lycopene, as other bioactive substances, presents stability issues with environmental conditions like heat, light, certain chemical reaction, pro‐oxidant conditions, among others (Pérez‐Masiá et al ., ; Hernández‐Almanza et al ., ), mostly related to the unsaturated bonds. Then, one of the major challenges is to establish an effective vehicle to deliver the appropriate nutritional components to the human body and decrease the changes that may result in deterioration or loss of its beneficial properties (Aguirre Calvo et al ., ; McClements, ), especially during processing.…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene is a naturally occurring red carotenoid pigment present in tomatoes, watermelon, pink grapefruit, pink guava and papaya (Sinha & Dua, ) with health benefits associated with lower risk of some degenerative diseases that may play a specific role in preventing prostate cancer and cardiovascular disease (Costa‐Rodrigues et al ., ). Lycopene, as other bioactive substances, presents stability issues with environmental conditions like heat, light, certain chemical reaction, pro‐oxidant conditions, among others (Pérez‐Masiá et al ., ; Hernández‐Almanza et al ., ), mostly related to the unsaturated bonds. Then, one of the major challenges is to establish an effective vehicle to deliver the appropriate nutritional components to the human body and decrease the changes that may result in deterioration or loss of its beneficial properties (Aguirre Calvo et al ., ; McClements, ), especially during processing.…”
Section: Introductionmentioning
confidence: 99%
“…Nunes & Mercadante (), on the other hand, reported that 50% was incorporated into cyclodextrins (Nunes & Mercadante, ), whereas the results by Pérez‐Masiá et al . () varied from 1.3 to 75.2% depending on the method and polymer used.…”
Section: Resultsmentioning
confidence: 87%
“…Table 2.1 shows some examples of food ingredients that have been encapsulated using proteins. α-Linolenic acid (Gómez-Mascaraque and Lopez-Rubio, 2016), lycopene (Pérez-Masiá et al, 2015), cardamom essential oil (Mehyar et al, 2014), folic acid (Pérez-Masiá et al, 2015), probiotics (Gomez-Mascaraque et al, 2016;Lopez-Rubio et al, 2012) Caseins Animal (milk)…”
Section: Proteinsmentioning
confidence: 99%
“…Therefore, some of the previous discussion regarding the encapsulation of bioactive oils could be applied to carotenoids. In this sense, Pérez-Masiá et al (2015) showed that higher encapsulation efficiencies were obtained when lycopene (previously dissolved in a soy bean oil) was microencapsulated using a whey protein matrix as compared to carbohydrate-based matrices, such as dextran or chitosan. Robert et al (2003) also obtained higher encapsulation efficiencies for the main carotenoid pigments present in an oleoresin from rosa mosqueta upon spray-drying within gelatin capsules than using starch as wall material.…”
Section: Encapsulation Of Carotenoidsmentioning
confidence: 99%